Sunaura Taylor: Beasts of Burden. Animal and Disability Liberation. The New Press, New York 2017 (twarda oprawa, 260 stron) - Poks, Małgorzata (Zoophilologica. Polish Journal of Animal Studies, 2021)
Sunaura Taylor: Beasts of Burden. Animal and Disability Liberation, The New Press, New York 2017, twarda oprawa, 260 stron